Cost Allocation of Transmission Losses in Electric Market Mechanism - Hermagasantos Zein; Erwin Dermawan (Universitas Ahmad Dahlan, 2012)
This paper proposes a new method to calculate cost allocation of transmission losses based on a certain price of energy. A mathematic model is developed by manipulating of the network equation to separate losses. This model uses complex power injection and, does not use approximations and assumptions in determining the cost allocation of losses. The calculation begins from the results of load flow calculation and it is continued to calculate power distribution from a generator to every load and line. Finally, the separating of losses and cost allocation of losses are calculated. The proposed method is easy to be understood and applied. An illustration results on IEEE 14-bus system show that the method is consistent with expectancies and slightly different from several referenced methods.